Farmers' intention and decision to adapt to climate change: A case study in the Yom and Nan basins, Phichit province of Thailand - Noppol Arunrat (2018)
© 2016 Elsevier Ltd Adaptation at farm level is an effective measure to cope with global climate change. The study aims to clarify farmers' intentions and decisions regarding global climate change adaptation. Logistic regression models were used to examine the influences of socioeconomic factors and climate adaptation communication processes on farmers' decision to apply adaptation strategies against drought and flood. Specifically, for a thorough understanding of non-adapting farmers, the theory of planned behavior was incorporated, to assess these farmers' intention to adaptation. Results showed that farmers' perceptions were consistent with the weather data over a short period, reporting a rise in temperature and a greater decrease in precipitation. Agricultural experience, farm income, training, social capital, and effective climate adaptation communication were statistically significant in increasing the probability of farmers' adaptation. For farmers who do not perceive climate change but adapted nonetheless, social capital played a major factor, driving their belief in, and behavior to adaptation, of which the most important aspects were neighbors and peer groups. Farmers' intention to adapt was mostly affected by perceived behavioral control factors, followed by attitude and subjective norms. Therefore, successful policies to enhance farmers' perceptions and adaptive capacity can encourage both actual and intended adaptation farmers. Adaptation strategies require the participation of multiple players from all related sectors engaging with local communities and farmers.